Effects of cypermethrin (pyrethroid), glyphosate and chlorpyrifos (organophosphorus) on the endocrine and immune system of Salvator merianae (Argentine tegu) - Mestre, Ana Paula (2019)
Several geographical areas where Salvator merianae is distributed in Argentina are included in regions with agricultural activity and exposed to pesticide formulations. Some pesticides could affect defense mechanisms being able alter structures of some components of immune and endocrine systems. To assess the potential effects of pesticides in this reptile under seminatural conditions, on the immune system and endocrine responses in S. merianae we analyzed several blood parameters. Total (TWBCC), differential (DWBCC) white blood cells count, heterophils/lymphocytes index (H/L), lobularity index (LI), natural antibodies (NAbs) titres, complement system (CS), and corticosterone concentration were analyzed in animals exposed to a mixture of cypermethrin (25%), glyphosate (66.2%) and chlorpyrifos (48%) formulations. In addition, body size was considered in these analyzes. TWBCC and NAbs revealed lower values in organisms exposed to pesticides respect to a control indicating a possible immunosuppression effect. Besides, the LI showed a greater number of lobes in organism exposed demonstrating symptoms of chronic infection. In addition, we observed a reduced growth in these animals possibly related to a less energy investment in body mass to maintain an active defense against pesticides. Finally, we found high levels of plasma corticosterone in animals exposed to mix formulation that could demonstrate neuroendocrine axis activation. Other parameters like DWBCC, H/L index and activity of CS showed no differences in treated animals respect to control group, which could indicate low sensibility of these parameters to the concentration of pesticides used. Our results provide evidence of the toxic effects of pesticides on different immune system parameters, but also a trade-off among these parameters, corticosterone levels and growth. In this way, we can conclude that the formulated pesticides applied widely and constantly in the areas occupied by S. merianae, would be affecting its immune and endocrine systems and therefore its ability to defend against external agents. This kind of studies is of great interest to know the possible responses of wild species to anthropogenic disturbances such as pesticide contamination.